Blockade efficacy of MEK/ERK-dependent autophagy enhances PI3K/Akt inhibitor NVP-BKM120's therapeutic effectiveness in lung cancer cells - Ren, Hui (Oncotarget, 2016)
NVP-BKM120 (BKM120) is a new pan-class I phosphatidylinositol-3 kinase (PI3K) inhibitor and has been tested in clinical trials as an anticancer agent. In this study, we determined whether BKM120 induces autophagy and the impact of autophagy induction on BKM120's growth-inhibitory activity. BKM120 potently induced elevation of autophagosome-bound type II LC3 (LC3-II) protein, predominantly in cell lines insensitive to BKM120, thereby inducing autophagy. The presence of lysosomal protease inhibitor chloroquine further enhanced the levels of LC3-II. BKM120 combined with chloroquine, enhanced growth-inhibitory effects including induction of apoptosis, suggesting that autophagy is a protective mechanism counteracting BKM120's growth-inhibitory activity. Interestingly, BKM120 increased p-ERK1/2 levels. When blocking the activation of this signaling with MEK inhibitors or with knockdown of ERK1/2, the ability of BKM120 to increase LC3-II was attenuated and the growth-inhibitory effects including induction of apoptosis were accordingly enhanced, suggesting that the MEK/ERK activation contributes to BKM120-induced authophagy. In mouse xenograft model, we also found that the combination of BKM120 and PD0325901 synergistically suppressed cell growth in human lung cancer cells. Thus, the current study not only reveals mechanisms accounting for BKM120-induced autophagy, but also suggests an alternative method to enhance BKM120's therapeutic efficacy against non-small cell lung cancer(NSCLC) by blocking autophagy with either a lysosomal protease inhibitor or MEK inhibitor.